2022
DOI: 10.1177/11795484221105327
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to SARS-CoV-2 Vaccine among Heart Transplant Recipients: A Systematic Review

Abstract: Background Heart transplant (HTX) recipients are at a significantly higher risk of adverse clinical outcomes, due to chronic immunosuppression and co-existence of other chronic conditions, when contracting the SARS-CoV-2 infection. Although vaccination against SARS-CoV-2 is currently the most promising measure for the prevention of severe Coronavirus Disease 2019 (COVID-19) among solid organ transplant recipients, the extent of immune response and its protective efficacy among patients receiving HTX has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…Based on the literature, the percentage of HTX recipients achieving humoral immune response after two doses of SARS‐CoV‐2 vaccination ranges between 12% and 75% due to the high heterogeneity of the examined populations 10–13,23,24 . In our study, 62% of the HTX recipients became seropositive after two doses of the SARS‐CoV‐2 vaccine and 58% of the seronegative patients achieved seroconversion after a third, booster vaccination.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Based on the literature, the percentage of HTX recipients achieving humoral immune response after two doses of SARS‐CoV‐2 vaccination ranges between 12% and 75% due to the high heterogeneity of the examined populations 10–13,23,24 . In our study, 62% of the HTX recipients became seropositive after two doses of the SARS‐CoV‐2 vaccine and 58% of the seronegative patients achieved seroconversion after a third, booster vaccination.…”
Section: Discussionmentioning
confidence: 57%
“…[26][27][28] For those solid organ transplant recipients who do not have sufficient antibody titers after three vaccines, the ESOT suggests the administration of additional booster vaccine doses or the consideration of pre-exposure prophylaxis with monoclonal antibodies. 14 In vaccinated HTX recipients, the weaker immune response was related to older age, 10,23,28 male sex, 23 vaccination within the first 23 or second 28 year after HTX and MMF or MPA immunosuppressant therapy. 10,12,23,28 Studies of solid organ transplant recipients showed that predictive factors for humoral response after vaccination were male sex, a longer period between transplantation and vaccination, living donor status, and liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This differs from the results of several national cohort studies reporting a lower risk of severe outcomes following Omicron infection compared with Delta variant 3 , 4 . This discrepancy could be explained by the lower antibody response following vaccination associated with a waning over time of vaccine-induced immunity in HT recipients 8 , 9 . Indeed, only 24% of the patients from our cohort displayed antibody titers above the threshold of 260 BAU/mL at the time of COVID-19 diagnosis.…”
mentioning
confidence: 99%